Pembinaan dan Pengembangan Kompetensi Generik Calon Guru bagi Meningkatnya Daya Saing Berbasis Multiple Intelligences Theory (MIT) - Nelly Yusra; Rian Vebrianto (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2018)
The paper want to develop and strengthen the generic competence of MI/PGSD teachers to improve competitiveness based on Multiple Intelligences Theory (MIT). This research is research and development. Testing the validity and reliability of the research results, it is known that the croanbach alpha value of each construct of generic skills from the construct of learning skills, thinking skills, technology skills, estimating skills and facilitator skills is above 0.6 with each alpha croanbach value is 0.76, 0.76, 0.83, 0.84, and 0.79. and for each construct of various intelligence (MIT) from the construct of verbal linguistic intelligence (0.79), logical mathematical intelligence (0.83), spatial verbal intelligence (0.88), physical kinetic intelligence (0.82), musical intelligence (0.85), interpersonal intelligence (0.85), intrapersonal intelligence (0.79), naturalist intelligence (0.89) and spiritual (existential) intelligence (0.89). When for objective questions the reliability value of Kuder Richardson 20 is 0.73 and for the short questions the short essay is 0.78. Thus, instruments that have been developed and developed by researchers have good validity and reliability, this means that these instruments are credible and effective in improving generic skills and various intelligence (MIT) in the prospective teacher.